Early Implementation of Sport Science–ICSS Synergy with Youth and Teachers in Earthquake Disaster Education in Air Kemuning Village, Seluma - Bogy Restu Ilahi; Fina Hiasa; Willi Novrian; Muhammad Nuryogatama; Mohammad Qais Rezvani (DIKDIMAS : Jurnal Pengabdian Kepada Masyarakat, 2026)
Background: Communities in earthquake-prone areas often have limited access to practical disaster mitigation education, leading to low preparedness and high vulnerability. Existing programs tend to emphasize theoretical knowledge while neglecting physical readiness and community-based capacity building. Integrating sport science into disaster mitigation offers a holistic approach by enhancing physical fitness, motor coordination, and adaptive movement responses, while digital technology supports broader dissemination and sustainable engagement.Aims: This community service program aimed to improve earthquake preparedness and to strengthen community resilience in Air Kemuning Village, Seluma Regency, through sport science-based mitigation education supported by the Integrated Circuit Sport Science (ICSS) digital platform.Method: A participatory approach was applied through four stages: socialization, training, technology implementation, and continuous mentoring. Participants included 28 teachers, 124 elementary school students, and 20 Karang Taruna members, assisted by university students. Training focused on safe movement during earthquakes, physical preparedness exercises, basic post-disaster sport massage, and digital literacy. Program effectiveness was evaluated using pre-test and post-test instruments and descriptive analysis.Results: The results indicated a 31.7% increase in disaster preparedness knowledge among teachers and students. Karang Taruna members developed basic sport massage and digital skills, contributing to the creation of an ICSS website prototype featuring five educational contents and a local fitness service promotion feature. The program also strengthened collaboration among schools, youth organizations, and the community.Conclusion: The integration of sport science and digital technology enhances disaster preparedness, strengthens community resilience, and promotes local economic opportunities, while supporting SDGs 3, 4, 8, and 11.